Media war and institutional reaction. The first years of Figueroa Alcorta's government from the Municipality of Rosario (1906-1908) (Res Gesta, 2020)
The intra-oligarchic disputes aroused by the arrival of José Figueroa Alcorta to the presidency of the republic, with his “Institutional Reaction” program, have been reviewed on from various analytical perspectives focused mainly on capital sources. How were these tensions perceived by local actors, in spaces far from the federal capital and traversed by their own logic of construction and dispute of political power? The objective of this article is to recover the vision of the newspaper El Municipio, spokesperson for the Unión Cívica Radical in the city of Rosario, as one of the main references of the local press at the time. Due to its long existence, large number of sales and marketing in other urban centers, this newspaper is considered an ideal source for the case. By focusing the study on an actor far from the formal institutional channels of the political regime in those years, that had a strong sense of struggle for meanings before the public, and who made the “Media War” his favorite strategy, we try to contribute to expanding the looks on a significant conjuncture in the final stage of crisis of the conservative governments.
Keywords: Press; Argentine History; Radicalism; Conservatism